2015
DOI: 10.1016/j.molcel.2015.01.016
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Basis for the Activation and Inhibition of the UCH37 Deubiquitylase

Abstract: SUMMARY The UCH37 deubiquitylase functions in two large and very different complexes, the 26S proteasome and the INO80 chromatin remodeler. We have performed biochemical characterization and determined crystal structures of UCH37 in complexes with RPN13 and NFRKB, which mediate its recruitment to proteasome and INO80, respectively. RPN13 and NFRKB make similar contacts to the UCH37 C-terminal domain, but quite different contacts to the catalytic UCH domain. RPN13 can activate UCH37 by disrupting dimerization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(155 citation statements)
references
References 53 publications
5
148
0
Order By: Relevance
“…This interaction strongly inhibits UCH-L5 [67]. Similar to the UCH-L5 activator RPN13 (discussed earlier), INO80G contains a DEUBAD domain [60] and recent structural analyses revealed that it inhibits UCH-L5 by occupying the ubiquitin-docking site on the enzyme through an unique hairpin structure that is absent in the DEUBAD domain of activator RPN13 [65,66]. While the DEUBAD domain of RPN13 activates UCH-L5 by increasing its affinity for substrates, in INO80G it does the opposite and dramatically decreases the affinity for substrates.…”
Section: Negative Regulation Of Dubsmentioning
confidence: 77%
See 2 more Smart Citations
“…This interaction strongly inhibits UCH-L5 [67]. Similar to the UCH-L5 activator RPN13 (discussed earlier), INO80G contains a DEUBAD domain [60] and recent structural analyses revealed that it inhibits UCH-L5 by occupying the ubiquitin-docking site on the enzyme through an unique hairpin structure that is absent in the DEUBAD domain of activator RPN13 [65,66]. While the DEUBAD domain of RPN13 activates UCH-L5 by increasing its affinity for substrates, in INO80G it does the opposite and dramatically decreases the affinity for substrates.…”
Section: Negative Regulation Of Dubsmentioning
confidence: 77%
“…For example, recently determined UCH-L5/RPN13 structures give insights into the basic activation mechanisms of UCH-L5 [65,66], but do not explain the polyubiquitin hydrolysis activity of UCH-L5 as part of the proteasome. Similar challenges exist for other DUBs and can only be addressed by studying large holo-enzyme complexes over different activation states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] These regulatory proteins share a conserved domain (within both RPN13 and INO80G), the deubiquitinase adaptor (DEUBAD) domain. Our results indicate that UCH37-1 is more likely to bind to the ubiquitin-like (UBL) domain of UCH37, thereby disrupting its interaction with the Pru domain of RPN13, but not with the DEUBAD domain.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of His-UCH37 was gradually decreased to achieve more stringent conditions: 2 mg (rounds 2-5), 1 mg (rounds 6-10), and 0.5 mg (rounds [11][12][13][14][15]. The RNA-His-UCH37 complexes were then washed three times with phosphate-buffered saline (PBS) and eluted in binding buffer supplemented with imidazole (250 mm).…”
Section: Methodsmentioning
confidence: 99%